1987
DOI: 10.1128/jb.169.1.410-413.1987
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of competition-defective mutants of Rhizobium fredii

Abstract: We coupled Tn5 mutagenesis with a competition assay to isolate mutants of Rhizobium fredii USDA 257 that are defective in competition for nodulation of soybeans. Two mutants with single TnS inserts in the chromosome showed reduced competitiveness in vermiculite but were identical to the wild-type strain in symbiotic ptoperties when inoculated alone. Recombination of TnS and flanking genomic regions cloned from the mutants into the parent strain showed that TnS was responsible for the mutant phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Until now it has been unclear whether rhizobia have genes, the only function of which is the control of competitiveness. The study of McLoughlin et al (1987) showed that this suggestion could be very probable, since they managed to isolate 3 R. fredii mutants in which alteration in Cmp-phenotype was not accompanied by any other alterations. However, these mutants were not characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…Until now it has been unclear whether rhizobia have genes, the only function of which is the control of competitiveness. The study of McLoughlin et al (1987) showed that this suggestion could be very probable, since they managed to isolate 3 R. fredii mutants in which alteration in Cmp-phenotype was not accompanied by any other alterations. However, these mutants were not characterized in detail.…”
Section: Discussionmentioning
confidence: 99%
“…These plasmids and other nonsymbiotic (cryptic) plasmids have also been implicated in other parts of the symbiotic interaction, such as the synthesis of bacteriocins (Hirsch, 1979) or the speed and efficiency of nodule initiation, and consequently could also be involved in a strain's competitiveness (Brewin et al, 1983;McLoughlin et al, 1987). Several authors have attempted to correlate the presence of a cryptic plasmid with the competitive ability of a strain.…”
Section: Genetic Exchange In the Fieldmentioning
confidence: 98%
“…McLoughlin et al, (1987) compared 600 random Tn5 mutants of R. fredii, and found four that exhibited reduced competitiveness. Unfortunately, they were unable to identify the physiological functions of the genes involved.…”
Section: Via6 Uncharacterized Factorsmentioning
confidence: 99%